Targeting Oxidative Stress as a Therapeutic Approach for Idiopathic Pulmonary Fibrosis - Estornut, Cristina; Milara, Javier; Bayarri, María Amparo; Belhadj, Nada; Cortijo, Julio (Frontiers in Pharmacology, 2022)
Idiopathic pulmonary fibrosis (IPF) is a chronic interstitial lung disease characterized by an abnormal reepithelialisation, an excessive tissue remodelling and a progressive fibrosis within the alveolar wall that are not due to infection or cancer. Oxidative stress has been proposed as a key molecular process in pulmonary fibrosis development and different components of the redox system are altered in the cellular actors participating in lung fibrosis. To this respect, several activators of the antioxidant machinery and inhibitors of the oxidant species and pathways have been assayed in preclinical in vitro and in vivo models and in different clinical trials. This review discusses the role of oxidative stress in the development and progression of IPF and its underlying mechanisms as well as the evidence of oxidative stress in human IPF. Finally, we analyze the mechanism of action, the efficacy and the current status of different drugs developed to inhibit the oxidative stress as anti-fibrotic therapy in IPF.